PROPERTIES OF REFINED NATURAL ASPHALT BUTON (ASBUTON) as PAVEMENT MATERIALS - Furqon Affandi (Jurnal Jalan-Jembatan, 2005)
There are two main types of bitumen i.e. those which occur naturally and those which are by product of the fractional distillation of petroleum. One type of natural bitumen is natural rock asphalt. There is a large reserve of natural rock asphalt in Buton Island-South East Sulawesi Province, Indonesia ; containing a bitumen content of 5% to 30% with an average bitumen content of 20% and remainder of the material is solid mineral matter, usually limestone or sandstone. The natural rock asphalt is known as Asbuton abbreviation of Asphalt Batu Buton i.e. Rock asphalt from Buton Island. The size of deposit has been variously estimated at up to 200 million tonnes. The deposit is therefore an important national resource with the potential to improve the properties of petroleum bitumen to carry the current and ever increasing traffic and axle loads in the future, reduce need imported bitumen and generated export income. To get a better quality Asbuton product, research and development has been ongoing. Available refining process has been developed. The refining process reduces the mineral content to produce Refined Asphalt Buton that has a bitumen content around 60% and new process has been recently developed produce a "pure Refined Asphalt Buton" has bitumen content > 99%. These types process high consistency and homogeneity and allow a uniform high quality to be produced. The addition of Refined Asphalt Buton bitumen increases the "Softening Point" and lower the "Penetration" of petroleum bitumen 60/70 pe grade. The addition of 20% refined asphalt Buton and about 54% pure refined asphalt buton bitumen P40/60 and P60/80 increases the softening point frim 48,5oC to 55oC ; 58oC and 54oC respectively. The penetration decreases from 61 dmm to 46 dmm and 47 dmm respectively. Blends containing Refined Asphalt Buton are less temperature susceptible as indicated by increasing Penetration Index (PI) value. This will improve resistance of a mix to permanent deformation particularly in tropical climates as indicated from wheel tracking tetsand Unconfined Uniaxial loading test results. The addition of Refined Asbuton has a significant effect in improving the mix stiffness which will improve the load spreading in the mix stiffness by 1.2; 2.7; times for the mixes containing 20% and 54% Refined Asbuton in the blend binder. This is due to increase in containing 20% and 54% Refined Asbuton in the blend binder. This is due to increase in Softening Point and a reduction in Penetration. Increasing in the mix stiffness would be able to spread the traffic loads onto the under laying layers of the pavement over as wide an areas as possible. The latter would mean that the stresses and strains in the pavement would be kept to a minimum resulting in a longer life for the pavement.